PENINGKATAN KETERAMPILAN DASAR MENGAJAR GURU MELALUI SUPERVISI KLINIS DI SDN 1 MAGELUNG KABUPATEN KENDAL - Trimo, Trimo (Jurnal Penelitian Pendidikan, 2011)
This research is based importance of school principals in carrying out its role as supervisor of clinical supervision specifically for teachers to master basic skills teaching. Improvement of teachers to teach basic skills will lead to the creation of the learning process multimakna. School action research aims to improve teachers teaching basic skills through clinical supervision so that the teacher has a set of capabilities to design an active learning process, creative, effective, enjoyable, and innovative. The method used is the school action research conducted 2 (two) cycles, with research subjects teachers SDN 1 Magelung 12 people. Each cycle consists of the activities of planning, execution, observation, and reflection. Methods of data collection using observation, while the technique of data analysis using descriptive analysis techniques percentages. The results showed that through clinical supervision activities undertaken to improve the school head teachers to teach basic skills in at SDN 1 Magelung UPTD Dikpora District Office South Kaliwungu Kendal regency school year 2010/2011. This can be known from an average increase in basic teaching skills from the first condition for 68.79 increased to 78.41 in cycle 1 with ketercapain performance indicators by 25%, and in cycle 2 to 88.71 with the achievement of performance indicators by 92% .